Integrating training, practice, and reflection within a new model for Canadian medical licensure: a concept paper prepared for the Medical Council of Canada - Chan, Teresa M; Dowling, Shawn; Tastad, Kara; Chin, Alvin; Thoma, Brent (Canadian Medical Education Journal, 2022)
In 2020 the Medical Council of Canada created a task force to make recommendations on the modernization of its practices for granting licensure to medical trainees. This task force solicited papers on this topic from subject matter experts. As outlined within this Concept Paper, our proposal would shift licensure away from the traditional focus on high-stakes summative exams in a way that integrates training, clinical practice, and reflection. Specifically, we propose a model of graduated licensure that would have three stages including: a trainee license for trainees that have demonstrated adequate medical knowledge to begin training as a closely supervised resident, a transition to practice license for trainees that have compiled a reflective educational portfolio demonstrating the clinical competence required to begin independent practice with limitations and support, and a fully independent license for unsupervised practice for attendings that have demonstrated competence through a reflective portfolio of clinical analytics. This proposal was reviewed by a diverse group of 30 trainees, practitioners, and administrators in medical education. Their feedback was analyzed and summarized to provide an overview of the likely reception that this proposal would receive from the medical education community.